Comprehensive analysis of m6A-modified circRNAs in peritoneal metastasis of high grade serious carcinoma of ovary - Guo, Lin; Xu, Nini; Qiu, Daner; Yang, Xiaozhe; Zhao, Shasha; Zhao, Hongxi (Frontiers in Oncology, 2022)
Purpose High-grade serous ovarian cancer (HGSOC) remains the most lethal female cancer due to metastasis. CircRNAs are recently identified to be modified by N6-methyladenosine (m6A) in many cells. However, the significance of m6A-modified circular RNAs (circRNAs) has not been elucidated in HGSOC peritoneal metastasis. Here, we aimed to investigate the participation and potential functions of m6A-modified circRNAs in HGSCO peritoneal metastasis. Methods Cancerous tissues were collected from the in situ and the peritoneal metastasis lesions of HGSCO patients. M6A-tagged circRNAs were identified by m6A-modified RNA immunoprecipitation sequencing (m6A-RIP-seq). Gene Ontology (GO) annotation and Kyoto Encyclopedia of Genes and Genomes (KEGG) pathway enrichment analyses were performed to predict the potential functions of the m6A-modified circRNAs. Results For the m6A-modified circRNAs, 259 were upregulated and 227 were downregulated in the peritoneal metastasis than in the situ lesions of HGSCO patients. For the m6A peaks, 1541 were upregulated and 1293 were downregulated in the peritoneal metastasis than in the in situ lesions of HGSCO patients. For the differential expressed circRNAs, 1911(19.6%) were upregulated and 2883(29.6%) were downregulated in the peritoneal metastasis than in the in situ lesions of HGSCO patients. The upregulated m6A-modified circRNAs were associated with the HIF-1 signaling. The downregulated m6A-modified circRNAs were associated with the MAPK signaling. Conclusions This work firstly identified the transcriptome-wide map of m6A-modified circRNAs in peritoneal metastasis of HGSCO. Our findings provided novel evidences about the participation of m6A-modified circRNAs via HIF-1 and MAPK signaling and a new insight in molecular target of HGSCO peritoneal metastasis.